2019
DOI: 10.1186/s40856-019-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of military expenditure on economic growth: evidences from India Pakistan and China using cointegration and causality analysis

Abstract: The study revisited the existing evidences of India Pakistan and China with updated data on the effect of military expenditure on economic growth. Econometric approaches analyzed the short and long run relationship between GDP growth and Military expenditure. Empirical studies have been done using cointegration analysis and causality test to justify the relationship and causality of the variables. Interestingly, study obtained positive log-run relation, no short run relationship and unidirectional long run cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…In other words, it was found that increasing military expenditures increased the economic growth. Our findings are parallel with the results of the studies conducted by Benoit (1978), Dunne et al (2001), Destek and Okumuş (2016), Raju and Ahmed (2019), and Laniran and Ajala (2021) in the literature. Technological changes in defense sector increase the total factor productivity and thus contribute to the development of manufacturing industries.…”
Section: Analysis and Findingssupporting
confidence: 91%
“…In other words, it was found that increasing military expenditures increased the economic growth. Our findings are parallel with the results of the studies conducted by Benoit (1978), Dunne et al (2001), Destek and Okumuş (2016), Raju and Ahmed (2019), and Laniran and Ajala (2021) in the literature. Technological changes in defense sector increase the total factor productivity and thus contribute to the development of manufacturing industries.…”
Section: Analysis and Findingssupporting
confidence: 91%
“…One of the latest studies based on the above relationship was conducted by Raju et al (2019) using cointegration and causality test on the panel data of three South Asian countries. The findings of the study suggested that there is a positive long-run relationship between military expenditure and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The short-run result showed that military spending and the number of persons in the military had a positive and significant link with economic growth. Raju and Ahmed (2019) used the Engle-Granger cointegration technique in a similar study to investigate the short-run and long-run nexus between military spending and economic growth in India, Pakistan and China using 1980-2017, 1989-2017and 1989-2017 respectively as ranges of data. The long-run results showed that military spending had a positive relationship with economic growth in the three countries.…”
Section: Empirical Literaturementioning
confidence: 99%